A high-density tungsten boride-based gamma-ray and neutron composite shielding material and a preparation method thereof

CN122930599APending Publication Date: 2026-10-16SOUTHWESTERN INST OF PHYSICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611109359.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

其中,单纯提高温度或延长保温时间往往会带来晶粒异常长大、能耗升高和组织不均等问题

Benefits of technology

1、本发明实施例提供的一种高致密度硼化钨基γ射线和中子复合屏蔽材料及其制备方法,在硼化钨基体中添加稀土氧化物,能够综合提高硼化钨材料的热中子、快中子、高能中子和伽马射线等复合屏蔽性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930599A_ABST
    Figure CN122930599A_ABST
Patent Text Reader

Abstract

The application discloses a high-density tungsten boride-based gamma-ray and neutron composite shielding material and a preparation method thereof. The composite material comprises the following components in percentage by mass: 80-95% of tungsten boride powder, 3-20% of rare earth oxide powder and 0.5-8% of metal activation sintering aid. The metal activation sintering aid is at least one selected from Ni, Cr, Fe and Co. The application can form a transient liquid phase or a high-diffusion interface layer in the early sintering stage by introducing specific elemental metal powder as the metal activation sintering aid, thereby enhancing the particle wetting and rearrangement capacity, improving the interface bonding state between the tungsten boride particles and the rare earth oxide particles, ensuring that the rare earth oxide is introduced to improve the shielding performance of the material while achieving full densification, and thereby significantly improving the density, shielding performance and comprehensive mechanical properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radiation protection materials technology, and more specifically, to a high-density tungsten boride-based gamma-ray and neutron composite shielding material and its preparation method. Background Technology

[0002] In nuclear engineering, radioactive source transportation, nuclear medicine protection, irradiation device maintenance, and special equipment protection, engineering components often face both gamma-ray and neutron radiation environments. Gamma-ray shielding typically relies on high atomic numbers and high-density compositions, while neutron shielding emphasizes moderation, absorption, and capture mechanisms. Therefore, a single material often cannot simultaneously meet the shielding requirements of both types of radiation. For components that serve both shielding and structural functions, materials also need to possess high density, low porosity, high mechanical strength, and good dimensional stability.

[0003] W has a high atomic number, providing excellent shielding against gamma rays and moderating high-energy neutrons. Boron, on the other hand, has a large neutron absorption cross-section. Therefore, tungsten boride is currently the preferred material for composite gamma and neutron shielding. However, tungsten boride is a ceramic material, which is hard but brittle, making it almost impossible to form using conventional metalworking methods at room temperature, thus making it extremely difficult to process into the required components.

[0004] Rare earth oxides, especially Gd2O3, can significantly improve gamma ray and neutron shielding performance because Gd has a high thermal neutron absorption cross section and a high atomic number. Introducing it into tungsten boride can comprehensively improve the composite shielding performance of thermal neutrons, fast neutrons, high-energy neutrons and gamma rays.

[0005] However, tungsten boride is a difficult-to-sinter system with strong covalent bond characteristics and low interparticle self-diffusion rate, making it difficult to achieve sufficient densification under conventional solid-state sintering conditions. On the other hand, rare earth oxides such as Gd2O3 are high-melting-point oxides. Although their introduction is beneficial to improving thermal neutron absorption performance, it will further increase the number of heterogeneous interfaces, leading to problems such as difficulty in particle rearrangement, residual interfacial pores, and local stress concentration, resulting in a decrease in material density and thus affecting the overall performance of the material.

[0006] In existing technologies, common methods to improve the density of such materials mainly include increasing the sintering temperature, extending the holding time, introducing sintering aids, or using external pressure sintering. However, simply increasing the temperature or extending the holding time often leads to problems such as abnormal grain growth, increased energy consumption, and uneven microstructure.

[0007] Therefore, there is an urgent need to propose a novel activation sintering method suitable for tungsten boride-rare earth oxide systems to achieve high density, high strength, and good comprehensive shielding performance of the material.

[0008] In view of the above, this application is hereby submitted. Summary of the Invention

[0009] Tungsten boride, as a composite gamma and neutron shielding material, generally exhibits poor thermal neutron shielding performance. Although the introduction of rare earth oxides can comprehensively improve shielding performance, the tungsten boride-rare earth oxide system suffers from problems such as difficulty in densification, numerous interfacial pores, insufficient mechanical strength, and low stability in engineering manufacturing. To address these technical issues, this invention provides a high-density tungsten boride-based gamma-ray and neutron composite shielding material and its preparation method. By introducing specific elemental metal powders as metal activating sintering aids and combining them with hot pressing sintering, a transient liquid phase or highly diffused interface layer can be formed in the early stage of sintering. This enhances the wetting and rearrangement capabilities between tungsten boride ceramic particles and rare earth oxide particles, improves the interfacial bonding state between particles, and ensures that the composite shielding material achieves sufficient densification while improving shielding performance through the introduction of rare earth oxides, thereby significantly improving the material's density, shielding performance, and comprehensive mechanical properties.

[0010] This invention is achieved through the following technical solution: In a first aspect, the present invention provides a high-density tungsten boride-based gamma-ray and neutron composite shielding material, comprising, by mass percentage: 80-95% tungsten boride powder, 3-20% rare earth oxide powder, and 0.5-8% metal activating sintering aid; The metal activating sintering aid is selected from at least one of Ni, Cr, Fe, and Co.

[0011] This invention adds rare earth oxides to a tungsten boride matrix, which comprehensively improves the composite shielding performance of tungsten boride materials against thermal neutrons, fast neutrons, high-energy neutrons, and gamma rays. Simultaneously, by introducing specific elemental Ni, Cr, Fe, and Co metal powders as metal activating aids with low melting points, this invention can produce "liquid-phase sintering," forming a transient liquid phase or highly diffusive interface layer that encapsulates ceramic particles and fills pores, optimizing and enhancing particle wetting and rearrangement capabilities. This allows for lower sintering temperature while increasing density and improving the interfacial bonding between tungsten boride particles and rare earth oxide particles. Ni, Fe, and Co are beneficial for forming a localized low-melting liquid phase or transient liquid phase wetting layer during the sintering activation stage, while Cr can participate in interface activation and grain boundary strengthening as a composite component. This significantly improves the sintering activation degree of the tungsten boride-rare earth oxide system, ensuring that the introduction of rare earth oxides improves the material's shielding performance while achieving sufficient densification, thereby significantly improving the material's density, shielding performance, and overall mechanical properties.

[0012] In one specific embodiment, the rare earth oxide powder includes at least one of Gd2O3, Dy2O3, Sm2O3, and Eu2O3.

[0013] In a specific embodiment, the rare earth oxide powder is preferably Gd2O3. Compared with other rare earth oxides, Gd element in Gd2O3 has a higher thermal neutron absorption cross section and atomic number. Therefore, the improvement of thermal neutron shielding performance after introducing tungsten boride matrix is ​​more significant. At the same time, the addition of Gd2O3 can further inhibit grain growth and play a role in refining grains. Therefore, Gd2O3 is preferred.

[0014] In one specific embodiment, the tungsten boride powder includes at least one of W2B, WB, WB2, W2B5, and WB4. In actual preparation, a mixture of two or three of WB, WB2, and W2B5 can also be used to improve the sintering density in terms of particle size distribution and sintering packing efficiency.

[0015] In one specific embodiment, the median particle size of the tungsten boride powder and Gd2O3 powder is 1-3 mm, which can ensure the uniformity of mixing, contact area and driving force for subsequent sintering.

[0016] Secondly, the present invention provides a method for preparing a high-density tungsten boride-based γ-ray and neutron composite shielding material, comprising the following steps: S1. Weigh out tungsten boride powder, rare earth oxide powder and metal activating sintering aid according to the formula, and dry and dehumidify each powder to remove adsorbed water and volatile impurities. S2. Place the above raw materials in a ball mill container, add anhydrous ethanol or isopropanol as a dispersion medium, and mix them using a planetary ball mill or a drum ball mill for 4 to 16 hours. After ball milling, the median particle size of the mixed powder is preferably controlled to be 1 to 3 mm. S3. Dry the ball-milled slurry to obtain a mixed powder with good flowability; if necessary, a small amount of temporary binder may be added to improve the subsequent pre-compression molding properties. S4. The uniformly mixed powder is placed into a high-strength mold according to a predetermined size, pre-pressed at room temperature and the gas in the powder is discharged. Preferably, the mold is a high-strength graphite mold. S5. Place the mold in a hot press furnace for vacuum hot pressing and sintering. The specific process is as follows: First, the temperature is raised to 1400–1600℃ and held for 10–120 min to allow the metal activating sintering aid to form a transient liquid phase, a local low-melting-point wetting layer, or a high-diffusion activation layer at the particle contact interface, thereby promoting particle rearrangement and interfacial pore filling. Then, the temperature is raised to 1750–1900℃ and held for 0.5–4 h to complete further densification and grain boundary strengthening. S6. While heating up, pressurize in one direction step by step, with a pressure of 5-15MPa. S7. After sintering, control the cooling rate to avoid thermal stress concentration. The temperature can be reduced to a certain level at a controlled rate, and then cooled to room temperature in the furnace before removing the mold for demolding. Alternatively, demolding can be performed under inert gas protection to prevent oxidation of the mold.

[0017] S8. Cut, grind, chamfer or finish the surface according to the component requirements to obtain plate, cylindrical, ring or irregular shielding components of the target size.

[0018] In a specific implementation, when a temporary binder is introduced into the system, the vacuum hot pressing sintering process is as follows: First, heat the material at 0.5–3℃ / min to 300–700℃ for degreasing and removal of organic matter, and hold for 0.5–3 h. Then, heat the material to 1400–1600℃ and hold for 10–120 min. After that, continue heating the material to 1750–1900℃ and hold for 0.5–4 h. While heating, the pressure is gradually increased in one direction to 5-15 MPa.

[0019] This invention employs a hot-pressing sintering process to achieve the co-sintering of tungsten boride and rare earth oxides, which can further and effectively solve the problems of weak interfacial bonding and pore concentration formed after the introduction of Gd2O3. This not only helps to improve the densification degree, but also achieves a composite system that balances structural strength and shielding performance.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention provides a high-density tungsten boride-based γ-ray and neutron composite shielding material and its preparation method. By adding rare earth oxides to the tungsten boride matrix, the composite shielding performance of the tungsten boride material against thermal neutrons, fast neutrons, high-energy neutrons and gamma rays can be comprehensively improved. 2. The present invention provides a high-density tungsten boride-based γ-ray and neutron composite shielding material and its preparation method. By introducing specific elemental Ni, Cr, Fe, and Co metal powders as metal activating aids, a transient liquid phase or high-diffusion interface layer can be formed in the early stage of sintering, optimizing and enhancing the particle wetting and rearrangement ability, improving the interfacial bonding state between tungsten boride particles and rare earth oxide particles, and ensuring that the introduction of rare earth oxides improves the material's shielding performance while achieving sufficient densification. The relative density can reach more than 98%, and the porosity can be reduced to 1-2%. 3. The high-density tungsten boride-based γ-ray and neutron composite shielding material and its preparation method provided in this embodiment of the invention use a metal activating sintering aid that can form a wetting layer at the particle interface, which helps to improve the bonding state of the heterogeneous interface, can significantly improve the sintering activation degree of the tungsten boride-rare earth oxide system, reduce the tendency of pore concentration and local brittle fracture, thereby increasing the compressive strength of the material by more than 40% compared with the system without sintering aid, thus comprehensively enhancing the density, shielding performance and comprehensive mechanical properties of the material; 4. The high-density tungsten boride-based γ-ray and neutron composite shielding material and its preparation method provided in this embodiment of the invention can separate the "interface activation" stage and the "high-temperature densification" stage by segmented sintering, which is beneficial to take into account both early particle rearrangement and later microstructure stability, and reduce the risk of abnormal grain growth caused by simply holding the material at high temperature for a long time.

[0021] 5. The present invention provides a high-density tungsten boride-based γ-ray and neutron composite shielding material and its preparation method. The resulting shielding composite material is suitable for manufacturing integrated shielding components for γ-rays, thermal neutrons, fast neutrons, and high-energy neutrons. It has high density, high composite shielding performance, good mechanical properties, and good engineering adaptability, and is suitable for the preparation of bulk, plate, thick-walled components and modular protection units. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 The XRD pattern provided in Embodiment 1 of the present invention; Figure 2 The SEM image provided in Embodiment 1 of the present invention; Figure 3 The XRD pattern provided in Embodiment 2 of the present invention; Figure 4 This is a SEM image provided in Embodiment 2 of the present invention; Figure 5 The XRD pattern provided for Comparative Example 1 of this invention; Figure 6 The SEM image provided for Comparative Example 1 of this invention; Figure 7 The XRD pattern provided for Comparative Example 2 of this invention; Figure 8 The SEM image provided for Comparative Example 2 of this invention. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments. The illustrative embodiments and descriptions of this invention are only used to explain this invention and are not intended to limit this invention.

[0025] In the following description, numerous specific details are set forth in order to provide a thorough understanding of the invention. However, it will be apparent to those skilled in the art that these specific details are not necessary to practice the invention. In other embodiments, well-known materials or methods have not been specifically described in order to avoid obscuring the invention.

[0026] Throughout this specification, references to “an embodiment,” “an example,” or “an example” mean that a particular feature, structure, or characteristic described in connection with that embodiment or example is included in at least one embodiment of the invention. Therefore, the phrases “an embodiment,” “an example,” “an example,” or “an example” appearing in various places throughout the specification do not necessarily refer to the same embodiment or example. Furthermore, specific features, structures, or characteristics can be combined in one or more embodiments or examples in any suitable combination and / or sub-combination. The term “and / or” as used herein includes any and all combinations of one or more of the associated listed items.

[0027] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0028] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0029] Example 1 This invention provides a method for preparing a high-density tungsten boride-based gamma-ray and neutron composite shielding material, comprising the following steps: S1. Weigh out the following by mass percentage: 92.0 wt.% WB powder, 5.0 wt.% Gd2O3 powder, and 3.0 wt.% Ni powder (additive). Dry and dehumidify each powder to remove adsorbed water and volatile impurities. S2. Place the above raw materials in a ball mill container, add anhydrous ethanol or isopropanol as a dispersion medium, and mix them using a planetary ball mill or a drum ball mill for 10 hours; the median particle size of the mixed powder is approximately 3 μm. S3. Dry the ball-milled slurry to obtain a mixed powder with good flowability; add 0.5 wt.% polyethylene glycol as a temporary binder to improve subsequent pre-compression molding properties. S4. The uniformly mixed powder is placed into a high-strength mold according to a predetermined size, pre-pressed at room temperature and the gas in the powder is discharged. Preferably, the mold is a high-strength graphite mold. S5. Place the mold in a hot press furnace for vacuum hot pressing and sintering. The specific process is as follows: The temperature was increased to 600℃ at a rate of 10℃ / min and held for 1 hour to remove organic residues; then the temperature was increased to 1600℃ at a rate of 5℃ / min and held for 60 minutes, with the pressure head gradually increased to 10MPa. S6. Then continue to heat to 1800℃ and hold for 2 hours; S7. Cooling with the furnace yields the composite shielding material.

[0030] The density of the composite shielding material sample was tested using the water displacement method, and the final sample density reached 96%.

[0031] The specific process of the drainage method is as follows: (1) Place the sample in a 105℃ oven and dry for 1-2 hours until the mass no longer changes. Then take it out and put it in a desiccator for later use. (2) Weigh the dried sample on a precision balance, i.e., the mass M1 of the sample in air; (3) Place the sample into a wide-mouth bottle and fill the bottle with deionized water. Use a vacuum pump to evacuate the bottle until the pores in the sample are filled with deionized water. (4) Gently place the sample into the self-made tray under the electronic balance, immerse it in deionized water, and weigh the sample mass M2; (5) Remove the sample from the immersion liquid, wipe off the excess liquid on the surface, and ensure that the liquid inside the sample cannot be extracted. Immediately weigh the saturated mass M3 in the air. According to Archimedes' principle, the formula for calculating the porosity of a sample is as follows: P = (M3 - M1) / (M3 - M2) × 100% M1 ------- The mass (g) of the sample in air after drying; M2 ------- The mass (g) of the sample in water after it has fully absorbed water; M3 ------- The mass (g) of the sample in air after it has fully absorbed water; The XRD results of the composite shielding material sample are as follows: Figure 1 As shown, the results indicate that the sintered sample phase mainly exists as a single WB phase, without the presence of gadolinium oxide phase, metal additive Ni, or other phases. This is because the content of metal additives is too low, and XRD is not sensitive to trace elements. At the same time, some metal atoms diffuse into the crystal lattice at high temperature to form a substitutional solid solution, without generating a new phase.

[0032] SEM images of composite shielding material samples, such as Figure 2 As shown, the number of pores at the grain boundaries is significantly reduced, and no obvious through-hole defects are observed.

[0033] The room temperature compressive strength of the composite shielding material sample (tested according to standard GB / T 4740-2024) is 1005 MPa. The weak bonding area in the fracture surface of the sample is significantly reduced, and the overall structure is more dense and continuous.

[0034] Gamma rays from composite shielding material samples 60 The linear attenuation coefficient of Co is 0.77 cm. -1 The macroscopic cross section of a 0.0253 eV thermal neutron is 143.4 cm. -1 The half-value layer thickness is 0.0048 cm; the macroscopic cross-section of the 14 MeV fast neutron is 0.302 cm. -1 The half-value layer thickness is 2.295 cm, indicating that it exhibits good synergistic attenuation capability for both types of radiation.

[0035] gamma rays 60Co linear attenuation coefficient measurement method: Place the sample in 60 After the Co gamma source, the attenuation ratio with and without the sample is measured, the protection efficiency is calculated, and then the linear attenuation coefficient is calculated by fitting the formula.

[0036] Example 2 This invention provides a method for preparing a high-density tungsten boride-based gamma-ray and neutron composite shielding material, comprising the following steps: S1. Weigh the following by mass percentage: 91.0 wt.% WB powder, 5.0 wt.% Gd2O3 powder, and 4.0 wt.% Ni powder. Dry and dehumidify each powder to remove adsorbed water and volatile impurities. S2. Place the above raw materials in a ball mill container, add anhydrous ethanol or isopropanol as a dispersion medium, and mix them using a planetary ball mill or a drum ball mill for 8 hours. S3. After ball milling, the slurry was dried at 80℃ for 12 h, and the median particle size of the resulting mixed powder was about 2.1 mm; a mixed powder with good flowability was obtained; 1 wt.% of polyethylene glycol was mixed as a temporary binder to improve the subsequent pre-compression molding properties. S4. The uniformly mixed powder is placed into a high-strength mold according to a predetermined size, pre-pressed at room temperature and the gas in the powder is discharged. Preferably, the mold is a high-strength graphite mold. S5. Place the mold in a hot press furnace for vacuum hot pressing and sintering. The specific process is as follows: Then, the temperature is increased to 650℃ at a rate of 10℃ / min and held for 1 hour to remove organic residues; then, the temperature is increased to 1600℃ at a rate of 5℃ / min and held for 60 minutes, with the pressure head gradually increased to 8 MPa. S6. Then continue to heat to 1800℃ and hold for 2 hours; S7. Cooling with the furnace yields the composite shielding material.

[0037] The density of the composite shielding material sample was tested using the water displacement method, and the final sample density reached 98%.

[0038] The XRD results of the composite shielding material sample are as follows: Figure 3 As shown, the results indicate that the sintered sample phase mainly exists as a single WB phase, with no gadolinium oxide phase, nor any metal additive Ni or other phases.

[0039] SEM images of composite shielding material samples, such as Figure 4 As shown, the grain boundaries are basically completely dense with no pores.

[0040] The room temperature compressive strength of the composite shielding material sample is 1296 MPa. The weak bonding area in the fracture surface of the sample is significantly reduced, and the overall structure is more dense and continuous.

[0041] Gamma rays from composite shielding material samples 60 The linear attenuation coefficient of Co is 0.765 cm. -1 The macroscopic cross section of a 0.0253 eV thermal neutron is 142.2 cm. -1 The half-value layer thickness is 0.0049 cm; the macroscopic cross-section of the 14 MeV fast neutron is 0.301 cm. -1 The half-value layer thickness is 2.302 cm, indicating that it exhibits good synergistic attenuation capability for both types of radiation.

[0042] Comparative Example 1 This comparative example provides a method for preparing a tungsten boride-based gamma-ray and neutron composite shielding material, comprising the following steps: Weigh 100% of WB powder and add it to anhydrous ethanol. Perform planetary ball milling for 8 hours using zirconia balls as the grinding medium. After milling, dry at 80℃ for 10 hours. The median particle size of the resulting mixed powder is approximately 3 mm.

[0043] WB powder was placed into a graphite mold, spread and compacted, and then placed in a hot pressing sintering furnace for vacuum hot pressing sintering. First, it was pre-pressed at room temperature, then heated to 500℃ at a rate of 10℃ / min and held for 1 hour to remove organic residues; then heated to 1400℃ at a rate of 5℃ / min and held for 60 minutes, with the pressure of the press head gradually increased to 5MPa. Finally, the temperature was further increased to 1750℃ and held for 2 hours before furnace cooling.

[0044] The density of the sintered sample was tested using the water displacement method, and the density was divided by the theoretical density to obtain a density of 95%; the XRD results are as follows. Figure 5 As shown, it mainly exists as a single phase in Western blotting (WB), with no other impurities; SEM results are as follows. Figure 6 As shown: The results indicate that the block is basically dense, with some areas containing tiny pores.

[0045] The material has a room temperature compressive strength of 1100 MPa; 100% WB bulk gamma ray... 60 The linear attenuation coefficient of Co is 0.827 cm. -1 The macroscopic cross section of a 0.0253 eV thermal neutron is 41.5 cm. -1 The half-value layer thickness is 0.0167 cm; the macroscopic cross-section of the 14 MeV fast neutron is 0.317 cm. -1 The half-value layer thickness is 2.184 cm.

[0046] Compared with Examples 1 and 2, this comparative example did not add rare earth oxide Gd2O3 and metal sintering aids. It can be seen that the gamma ray and 14MeV fast neutron shielding performance and compressive strength of this comparative example are comparable to those of Example 1. In Example 2, the increased content of metal sintering aids significantly improved the compressive strength, indicating that the addition of Gd2O3 and metal sintering aids not only did not degrade the original mechanical and shielding properties of tungsten boride, but also improved them through a reasonable ratio of Gd2O3 and metal sintering aids. Furthermore, the thermal neutron shielding performance of this comparative example is significantly lower than that of Example 1, especially the macroscopic cross-section of thermal neutrons is significantly reduced. This is because Gd2O3 is absent compared to the examples, indicating that the addition of Gd2O3 in the examples improved the material's thermal neutron shielding performance. Finally, the density of this comparative example is also significantly lower than that of Example 1, indicating that the addition of metal sintering aids solved the interfacial bonding problem caused by the introduction of Gd2O3, achieving dense co-firing of tungsten boride and rare earth oxides.

[0047] Comparative Example 2 This comparative example provides a method for preparing a tungsten boride-based gamma-ray and neutron composite shielding material, comprising the following steps: Weigh out the following by weight percentage: 95.0 wt.% WB powder and 5.0 wt.% Gd₂O₃ powder. Perform wet ball milling for 10 h using isopropanol as the dispersion medium. The median particle size of the resulting mixed powder is approximately 2.5 mm.

[0048] The mixed powder was placed into a graphite mold, spread and compacted, and then placed in a hot pressing sintering furnace for vacuum hot pressing sintering. Pre-pressing was performed at room temperature, followed by heating to 520℃ at 10℃ / min and holding for 1 hour to remove organic residues; then heating to 1600℃ at 5℃ / min and holding for 60 minutes, with the pressure of the press head gradually increased to 10MPa; finally, the temperature was further increased to 1750℃ and held for 2 hours before furnace cooling.

[0049] The density of the sintered sample was tested using the water displacement method, and the density was divided by the theoretical density to obtain a density of 90%. XRD results of the sintered composite material bulk are as follows Figure 7 As shown, the results indicate that the phase exists as a single phase in Western blotting (WB), with no gadolinium oxide phase or other impurity phases observed. SEM is shown below. Figure 8 As shown, the results indicate that there are tiny holes in some areas of the block.

[0050] The room temperature compressive strength is 845 MPa; the WB and gadolinium oxide composite shielding material has a bulk gamma ray resistance of 845 MPa. 60 The linear attenuation coefficient of Co is 0.785 cm. -1 The macroscopic cross section of a 0.0253 eV thermal neutron is 147.2 cm⁻¹. -1The half-value layer thickness is 0.0047 cm; the macroscopic cross-section of the 14 MeV fast neutron is 0.305 cm. -1 The thickness of the half-value layer is 2.272 cm.

[0051] Compared with Example 1, no metal sintering aid was added to this comparative example. It can be seen that although the shielding performance of the material in this comparative example is comparable to that of Example 1, its compressive strength and density are significantly lower than those of the example. This is because no metal sintering aid was added to this comparative example, so the heterogeneous interface between tungsten boride and Gd2O3 is difficult to bond, resulting in concentrated pores inside the material and the formation of more voids. This makes it impossible to achieve dense co-firing of tungsten boride and rare earth oxides, ultimately leading to local brittle fracture and reducing the mechanical properties of the material.

[0052] Meanwhile, compared with Comparative Example 1, the addition of Gd2O3 alone improved the shielding performance, but deteriorated the sintering density and mechanical properties of the material. This further illustrates that metal sintering aids play a key role in the dense sintering of the tungsten boride and Gd2O3 system.

[0053] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A high-density tungsten boride-based gamma-ray and neutron composite shielding material, characterized in that, By mass percentage, it comprises the following components: 80-95% tungsten boride powder, 3-20% rare earth oxide powder, and 0.5-8% metal activating sintering aid; The metal activating sintering aid is selected from at least one of Ni, Cr, Fe, and Co.

2. The high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 1, characterized in that, The rare earth oxide powder includes at least one of Gd2O3, Dy2O3, Sm2O3, and Eu2O3.

3. The high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 1, characterized in that, The rare earth oxide powder used is Gd2O3.

4. The high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 1, characterized in that, The tungsten boride powder includes at least one of W2B, WB, WB2, W2B5, and WB4.

5. The high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 1, characterized in that, The median particle size of the tungsten boride powder and Gd2O3 powder is 1–3 mm.

6. A method for preparing the high-density tungsten boride-based γ-ray and neutron composite shielding material according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Weigh out tungsten boride powder, Gd2O3 powder and metal activator, and dry and dehumidify them; S2. Mix the raw materials, add the dispersion medium, and perform ball milling. S3. After ball milling, the mixture is dried to obtain a well-flowing mixed powder. S4. Pre-press the mixed powder into shape at room temperature; S5. Perform vacuum hot pressing sintering.

7. The method for preparing the high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 6, characterized in that, In step S2, anhydrous ethanol or isopropanol is used as the dispersion medium, and the mixture is ball-milled using planetary ball milling or drum ball milling for 4 to 16 hours.

8. The method for preparing the high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 6, characterized in that, In step S5, the vacuum hot pressing sintering process is as follows: First, raise the temperature to 1400–1600℃ and hold for 10–120 min; then continue to raise the temperature to 1750–1900℃ and hold for 0.5–4 h.

9. In the preparation method of the high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 6, in step S5, the temperature is increased while the pressure is gradually increased to 5-15 MPa in one direction.

10. The method for preparing the high-density tungsten boride-based γ-ray and neutron composite shielding material according to claim 6, characterized in that, When pre-pressing mixed powders at room temperature, a temporary binder can be introduced. The specific vacuum hot pressing sintering process in this case is as follows: First, heat the material at 0.5–3℃ / min to 300–700℃ for degreasing and removal of organic matter, and hold for 0.5–3 h. Then, heat the material to 1400–1600℃ and hold for 10–120 min. After that, continue heating the material to 1750–1900℃ and hold for 0.5–4 h. While heating, the pressure is gradually increased in one direction to 5-15 MPa.